Phase Separation and Chemical Durability in the SiO2-B2O3-Na2O (SBN) Glass System - Aboutaleb, D.; Douglad, J.; Safi, B.; Jbara, O.; Iratni, A. (Asian Journal of Chemistry, 2011)
Sodium borosilicates glasses were treated isothermically several times. In present work, the effect of phase separation on chemical durability and the electric resistivity was investigated. In addition, the effect of chemical composition and addition of calcium on the kinetics and rate of leaching of these glass materials in hydrochloric acid (3M HCl) was also investigated. The system studied exhibited phase separation starting from 550 ºC. Present results showed that the chemical durability was weakened upon phase separation. On the other hand, chemical durability increased with increasing SiO2 content and reducing the alkaline oxides (Na2O) content. Results also showed a drastic decrease in the ionic electric conductivity (increase in resistivity) with decreasing C = (Na2O + B2O3)/SiO2 (reduction of Na2O). The effect of chemical composition on the rate of leaching showed that boron and sodium are dissolved much more quickly than silicon. The greater the content of Na2O and B2O3 in glass, the more soluble the glass becomes. However, addition of silica results a decrease in glass solubility. These results indicate that substitution of sodium by calcium induces an acceleration of the kinetics of deterioration.